PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Logam yang Terdaftar di Bursa Efek Indonesia Periode 2016-2019) - Dikdik Harjadi; Lili Karmela Fitriani; Nok Ayu Permata Sari (ITB AAS INDONESIA, 2022)
The purpose of this study was to determine the effect of Good Corporate Governance consisting of Independent Commissioners, Institutional Ownership, Managerial Ownership and the Effect of Corporate Social Responsibility on Profitability in Manufacturing companies listed on the Indonesia Stock Exchange from 2016-2019. The method used in determining the sample of this study is by using purposive sampling method, while the population of this study is manufacturing companies listed on the Indonesia Stock Exchange. Sampling by using purposive sampling is obtained a sample of 14 companies. This study uses secondary data obtained from financial reports published on the internet through the official website of the Indonesia Stock Exchange www.idx.com in 2016-2019. The method of analysis in this study is multiple regression analysis. The results of this study indicate that: (1) Independent Commissioner has a significant positive effect on profitability. (2) Institutional Ownership has a significant positive effect on Profitability. (3) Managerial Ownership has a significant positive effect on Profitability. (4) Corporate Social Responsibility has a significant positive effect on profitability. The estimation results show that the predictive ability of this model is 71.5% and the remaining 28.5% is influenced by other factors not examined.